Making Services Work for Poor People : The Role of Participatory Public Expenditure Management (PPEM) - World Bank (Washington, DC, 2012)
The public sector of most developing countries is often the target of numerous criticisms - lack of or no infrastructure, absenteeism of service providers like teachers and doctors, poor quality of services, corruption, non-transparency, favoritism, discrimination, etc. While several of these criticisms are usually attributed to lack of resources and the conflict between the needs of equity and those of efficiency, research has shown in general that the correlation between increased public expenditure and actual outcomes or improvements in service delivery is weak. This gap between spending and development outcomes reflects more serious deficiencies of 'voice' and 'accountability' for citizens in general, and the poor in particular. The need for making services work for poor people is therefore immense, and has provided the theme for the World Bank's World Development Report (WDR) for 2004.